Reinduction with Certolizumab Pegol in Patients with Crohn's Disease Experiencing Disease Exacerbation: 7-Year Data from the PRECiSE 4 Study. Issue 8 (August 2016) - Lee, Scott D.; Rubin, David T.; Sandborn, William J.; Randall, Charles; Younes, Ziad; Schreiber, Stefan; Schwartz, David A.; Burakoff, Robert; Binion, David; Dassopoulos, Themos; Arsenescu, Razvan; Gutierrez, Alexandra; et al.
Abstract : Background: Patients with Crohn's disease in whom tumor necrosis factor antagonist therapy fails have limited treatment options, and the benefit of reintroducing the same therapy remains unclear. Here, we report results from PRECiSE 4 (NCT00160706), an open-label extension study of certolizumab pegol in patients who withdrew from the placebo-controlled studies PRECiSE 1 or 2. Methods: Patients eligible for PRECiSE 4 had Crohn's disease exacerbation on placebo or primary or secondary failure to certolizumab pegol in PRECiSE 1 or 2, and received 400 mg certolizumab pegol subcutaneously at weeks 0, 2, and 4 and every 4 weeks thereafter up to 360 weeks. We assessed safety (adverse events) and efficacy (clinical remission) of extended certolizumab pegol therapy. Results: Patients enrolled in PRECiSE 4 (N = 310; mean age, 37 yr; 58% female; 95% white) had a mean Crohn's disease duration of 8.5 years before entering the qualifying studies. At weeks 52, 104, and 156, remission rates were 28.5%, 17.5%, and 12.6% by nonremitter imputation, and 63.8%, 60.0%, and 63.5% by observed cases, with 47.4%, 31.9%, and 23.2% of patients, respectively, remaining on therapy. By study end (7.5 yr), 92.3% of patients discontinued therapy, 49% on account of adverse events. No new safety signals emerged. Incidence rate (new cases)/100 patient-years was 6.11 for serious infections and 1.29 for malignancies. Conclusions: Certolizumab pegol was effective in many patients who previously discontinued certolizumab pegol for lack or loss of response. Thus, discontinuation of therapy may not always be necessary. Safety was consistent with previous findings.